Syndicate women : gender and networks in Chicago organized crime - Smith, Chris M. (University of California Press, 2019)
"Syndicate Women uncovers a unique historical puzzle: women composed a substantial part of Chicago organized crime in the early 1900s before Prohibition, but during Prohibition, when criminal opportunities increased for men and women, women were largely excluded from organized crime. The US prohibition of the production, transportation, and sale of intoxicating beverages, from 1920 to 1933, dramatically altered the criminal landscape. During Prohibition, Chicago organized crime tripled in size, became a more centralized organization, spread geographically, surged in profits, and left women behind. Syndicate Women solves this puzzle by interrogating relational theories, historical data, and criminal networks"--Provided by publisher.